Supply-side perspectives on outdoor tourism in the north of Portugal - Martins, Oliva M. D. (2022)
Nowadays, the tourism sector presents many opportunities and challenges. Outdoor Tourism (OT), due to the unusual situation experienced by the pandemic caused by COVID-19, maybe one of the main opportunities to promote the local development of tourist destinations. Most of the literature developed in this context has focused the demand side. Therefore, the investigation intended to fill this gap, considering the perspective of the supply side, taking into account a vision of sustainable development. To meet this gap, the main objective is to contribute to the characterization of Outdoor Tourism (OT) in the North of Portugal, and understand the potential of OT in the perspective of supply., thirty-eight tourist entertainment companies (TEC) were interviewed to assess supply and perceived customers? motivations. Of the seven Nomenclature of Territorial Units for Statistical Purposes (NUTS), the Northern region was considered to be an area with enormous potential for Nature-related tourist). For the supply side, seasonality and climate were identified as important factors supporting environment preservation. Radical experiences, adventure and getting out of the routine were identified as motivating demand factors, as well as the contact with Nature and the landscape. We have also observed that if we consider the stimulation of the local economy by OT, there is still a lot to do. The evidence pointed to some social imbalance, namely related to employability. Employees were hired according to the evolution of demand, which favours unemployment and social instability. Also, the tourists/costumers are the main channels of communication of the activities; the word-ofmouth (WOM) of costumers? experiences, personally or through online social media, takes on a prominent role. In this sense, tourists? online reviews, testimonies and word-of-mouth can be optimized through social networks and digital marketing. Finally, to evaluate the region's potential for the OT, the interviewees suggested integrating the players involved with the OT into a single network, supporting the activities and promoting the region.